Lexical representation of emotion of sadness (based on the material of poetic works by Lina Kostenko) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2018)
The article clarifies that the anthropocentric and emotional orientation of modern linguistic studies encourages researchers to study linguistic means of expressing emotions, since emotions most often form the motivational basis of personality activity; analyzes the nature of linguistic approach to the study of emotions, to understand category of emotivity and its place in the semantic structure of word; it is indicated that emotions are a subjective relation of a person to objects and phenomena of the surrounding reality; it is emphasized that emotionality is a semantic property of language with help of a system of various means to expressing emotionality as a fact of the psyche; reviewed features of the inertial and adherent emotionality of the linguistic units; it is stressed that sadness is a basic emotion that can accompany both positive (constructive) feelings and feelings of a person. In the proposed study are presented vocabulary classifications for the representation of emotions; It was found out that emotional value is the meaning in which the emotional content is expressed or defined; It was found out that emotional expression is expressed by a certain system of language means and their combination; It was established that the verbalization of emotion of sadness by lexical linguistic means is carried out with the help of a direct lexical-semantic nomination, means of word formation, individual author units and adherent emotions expressed by nouns, verbs, adjectives, adverbs and exclamations.
Keywords: emotional category; emotional vocabulary; lexical means of expressing emotions; adherent emotionality